Proceedings of the 2022 Working Group Reports on Innovation and Technology in Computer Science Education 2022
DOI: 10.1145/3571785.3574126
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the CS Student Learning Experience

Abstract: Students have experienced incredible shifts in their learning environments, brought about by the response of universities to the ever-changing public health mandates driven by waves and stages of the coronavirus pandemic (COVID-19). Initially, these shifts in learning (mode of course delivery, course availability, etc.) were considered emergency responses. However, as the pandemic pressed on, students have had to repeatedly adapt to the continuously evolving educational landscape.This working group builds upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
0
7
0
1
Order By: Relevance
“…Numerous voices from the educational community are calling to preserving the new options offered during distance learning and move toward more student-centered pedagogy [34][35][36][37][38][39]. Looking specifically at the CS landscape, Crick et al in [40] reported some students' interest toward post-pandemic online learning, although students in their study were also acutely aware of the risks, such as social isolation, and overall indicated preference toward including at least some face-to-face course activities.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous voices from the educational community are calling to preserving the new options offered during distance learning and move toward more student-centered pedagogy [34][35][36][37][38][39]. Looking specifically at the CS landscape, Crick et al in [40] reported some students' interest toward post-pandemic online learning, although students in their study were also acutely aware of the risks, such as social isolation, and overall indicated preference toward including at least some face-to-face course activities.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, as suggested by some of our interviewees, identifying core elements everyone should be learning and starting to characterise a subject-specific pedagogy would significantly contribute to the acceptance of CE in the context(s) of undergraduate CS programmes. Perhaps these types of changes will be increasingly feasible and tractable in a world in which we are trying to better understand the emerging impact and ramifications of generative AI [41,91] as part of a post-COVID "new normal" [23,27], where there is a renewed focus on high-quality learning, teaching and assessment, and specifically what this means for effective pedagogy and practice in CS and CE [106,107]. Ultimately, we hope that an open international community of practice will form around this work.…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%
“…Esto es aún más limitado cuando la experiencia de interacción es desde modos tradicionales, como videoconferencias en la pasividad del estudiante, es decir, centrado más en la enseñanza que en el aprendizaje. Esta situación suele ocurrir cuando no se adapta de forma efectiva la tecnología con estrategias didácticas contextualizadas para que el estudiante sea protagonista de su proceso de aprendizaje (Abreu, 2020;Siegel et al 2022).…”
Section: Condicionantes De La Educación Remotaunclassified